2022
DOI: 10.1128/msystems.00157-22
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity and Interaction Specificity in Kombucha Tea Fermentations

Abstract: Through an integration of metagenomic and experimental approaches, our work reveals the diversity and nature of interactions among key taxa in kombucha microbiomes through the construction of synthetic microbial pairs. Manipulation of these microbes in kombucha has the potential to shape both the fermentation qualities of kombucha and the production of biofilms and is valuable for kombucha beverage producers, biofilm engineers, and synthetic ecologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 45 publications
4
34
1
Order By: Relevance
“…In the study of [12], a consistent cellulosic biofilm was only formed with a native kombucha consortium; in the co-cultures of selected strains, the biofilm was not present. Using two different yeast species, Zygosaccharomyces bisporus and B. bruxellensis, in pairwise combinations with K. rhaeticus, the production of biofilm was remarkably higher with B. bruxellensis than with Z. bisporus [23], thus opposite of this study where more cellulose was recovered from NhZp than NhBb.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In the study of [12], a consistent cellulosic biofilm was only formed with a native kombucha consortium; in the co-cultures of selected strains, the biofilm was not present. Using two different yeast species, Zygosaccharomyces bisporus and B. bruxellensis, in pairwise combinations with K. rhaeticus, the production of biofilm was remarkably higher with B. bruxellensis than with Z. bisporus [23], thus opposite of this study where more cellulose was recovered from NhZp than NhBb.…”
Section: Discussioncontrasting
confidence: 85%
“…In both co-cultures, a decrease of ethanol was observed as compared with the monocultures, associated with the production of acetic acid from ethanol promoted by Nh [8]. A divergent result was found by [23], who reported a strikingly higher ethanol production by B. bruxellensis than Z. bisporus.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The most dominant bacteria in kombucha was Komagateibacter, a member of Acetobacteraceae family (Chakravorty et al, 2016). Another metagenomic approach showed that bacteria Komagataeibacter rhaeticus and yeast Brettanomyces bruxellensis were the most common microorganism in 23 samples of kombucha across the United States (Landis, et al,2022) Our previous research, focused on cultivation approach, has also reported that culturable microorganisms from kombucha drink (liquid phase) were all bacteria. Four out of six bacteria isolates showed close characteristic to Acetobacter genus (gram negative, short rod, motile, and does not produce endospore) (Permana, et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…AAB can always be found during the fermentation of vinegar and kombucha (Landis et al., 2022; Lynch et al., 2019). The main AAB genera include Acetobacter , Acidomonas , and Amukamara (Lynch et al., 2019).…”
Section: Microbial Community Assembly Of Sffmmentioning
confidence: 99%